Colombia : Financial Sector Assessment Program-Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report, 2018)
This report provides a summary of the anti-money laundering/combating the financing of terrorism (AML/CFT) measures in place in Colombia as at the date of the onsite visit (June 5 to 22, 2017). It analyzes the level of compliance with the Financial Action Task Force (FATF) 40 Recommendations and the level of effectiveness of Colombia's AML/CFT system, and provides recommendations on how the system could be strengthened.